Rising powers and foreign policy revisionism : understanding BRICs identity and behavior through time - Thies, Cameron G.; Nieman, Mark David (University of Michigan Press, 2018)
"In Rising Powers and Foreign Policy Revisionism, Cameron Thies and Mark Nieman examine the identity and behavior of the BRICS (Brazil, Russia, India, China, and South Africa) in light of concerns that rising powers may become more aggressive and conflict-prone. The authors develop a theoretical framework that encapsulates pressures for revisionism through the mechanism of competition, and pressures for accommodation and assimilation through the mechanism of socialization. The identity and behavior of BRICS should be a product of these two forces as mediated by their domestic foreign policy processes. State identity is investigated qualitatively by using role theory and identifying national role conceptions, while economic and militarized conflict behavior are examined using Bayesian change-point modeling, which identifies structural breaks in a time series of data revealing potential wholesale revision of foreign policy. Using this innovative approach to show the behavior of rising powers is not simply governed by the structural dynamics of power, but also by the roles these rising powers define for themselves, they assert this process will likely lead to a much more evolutionary approach to foreign policy and will not necessarily generate international conflict"--